BS EN 4035. Aerospace series. Rod end, adjustable, with self-aligning double row ball bearing, in corrosion resisting steel, reduced internal radial clearance and threaded shank in titanium alloy. Dimensions and loads. (22nd July 2020) - British Standards Institution,
No abstract available